2010
DOI: 10.2214/ajr.09.3375
|View full text |Cite
|
Sign up to set email alerts
|

Hypervascular Liver Masses on Contrast-Enhanced Ultrasound: The Importance of Washout

Abstract: Hypervascular malignant lesions show washout except infrequent cases of HCC. Rapid washout characterizes metastases, whereas HCCs show variable, often slow, washout. However, washout is not unique to malignancy and may be seen in benign lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
106
1
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(119 citation statements)
references
References 34 publications
(34 reference statements)
7
106
1
5
Order By: Relevance
“…The replenishment intensity time-course can be quantified with high mechanical index imaging with disruption of microbubbles within the field of view [32]. In HCC, arterial phase vascularization and portal phase washout is seen, typically less rapidly than hypervascular metastases as shown in a study of 146 hypervascular lesions [33]. CEUS has been utilized in several studies for the evaluation of therapeutic response, for example to TACE, where retention of hyperattenuating Lipiodol may mask residual tumour: one study of 29 nodular HCCs showed that CEUS was more sensitive but had a lower specificity than CECT with sensitivity and specificity of 93% and 65% and 64% and 100% respectively, where conventional angiography was the gold standard [34].…”
Section: Assessment Of Tumour Vascularizationmentioning
confidence: 99%
“…The replenishment intensity time-course can be quantified with high mechanical index imaging with disruption of microbubbles within the field of view [32]. In HCC, arterial phase vascularization and portal phase washout is seen, typically less rapidly than hypervascular metastases as shown in a study of 146 hypervascular lesions [33]. CEUS has been utilized in several studies for the evaluation of therapeutic response, for example to TACE, where retention of hyperattenuating Lipiodol may mask residual tumour: one study of 29 nodular HCCs showed that CEUS was more sensitive but had a lower specificity than CECT with sensitivity and specificity of 93% and 65% and 64% and 100% respectively, where conventional angiography was the gold standard [34].…”
Section: Assessment Of Tumour Vascularizationmentioning
confidence: 99%
“…Often HCCs are hyperenhanced in the arterial phase, with an irregular or a chaotic pattern [45] that is influenced by the lesion's size [46] with mild, late, or very late "wash-out". The timing of "wash-out" is correlated with the differentiation of the tumor, therefore CEUS examination of the HCC should take a least fourfive minutes [47][48][49]. Specific algorithms have been developed, such as CEUS LI-RADS [https://www.acr.org/ Quality-Safety/Resources/LIRADS/CEUS-LIRADS], in order to standardize the reporting system and the diagnostic decision in HCC.…”
Section: Livermentioning
confidence: 99%
“…Negative enhancement or ‘washout’ during the PVP is also an important characteristic of HCC as typical tumors lack a portal venous supply. Washout of HCC in the PVP, however, is often not obvious until late (>90 s) and is generally slower and milder than that of liver metastasis [18]. Benign nodules such as regenerative nodules or dysplastic nodules are usually isoechoic or slightly hypoechoic in the HAP and PVP.…”
Section: Us Imagingmentioning
confidence: 99%